ENVIRONMENTAL AWARENESS INSPIRES NOR ATHIRAH TO PRODUCE 'PAPER CRANES' - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 12 October 2016 – Having the awareness on environmental issues and how they would affect future generations has inspired Nor Athirah Md Ghazali with the idea for her artwork entitled 'Paper Cranes', which won third prize in the Vision Petron 2016 National Students Art Competition.